Pemimpin di Era Digital: Membangun Kinerja Pegawai Melalui Iklim Organisasi - Maximinus Saverius Susanto; Mansyur Abdul Hamid; Imaculata Fatima (Intitut Agama Islam Nasional Laa Roiba Bogor, 2026)
Public sector digital transformation calls for leadership combining human-centric human resource management with technology utilization. But especially in local government settings, empirical data on the immediate impact of digital leadership on employee performance remain contradictory. By setting organizational climate as a mediating variable in public sector digital transformation, this study investigates the influence of digital leadership on staff performance. Employing a survey of civil servants in the Government of Ende Regency in Indonesia, a quantitative methodology was adopted. Partial Least Squares–Structural Equation Modeling (PLS-SEM) helped to examine the data. The findings show that employee performance is not directly much affected by digital leadership. Conversely, digital leadership has a beneficial and statistically significant impact on corporate culture, which then has a notable positive effect on employee productivity. Moreover, the organizational environment entirely mediates the association between digital leadership and staff performance. These results point to the development of an adaptive, collaborative, and supportive organizational environment as the way through which digital leadership's impact is realized—not right away but over time. Theoretically, this research adds to the body of public sector digital leadership by pointing at organizational environment as a major causal agent linking leadership and performance. Practically, the results point to the need of conscious efforts to create a favourable organizational environment to guarantee successful public sector digital transformation along with the enhancement of digital leadership.